Kitâb al Muḥâwarah al Hadîthah Al Juz’u al Awwal: Taḥlîl al Muḥtawa inda Naẓahriyyah Nâṣir Abd al Ghâli - Safitri, Intan; Thohir, Muhammad; Hanifah, Umi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Objective- This study aims to find out whether the book Muhawaratul Haditsah first chapter complies with the four criteria for teaching materials put forward by Abdul Ghali and whether this book is suitable for learning Arabic. Design / Methodology / Qualitative- This research uses the documentation method or what is often referred to as library research or library research with a content analysis approach. What was used to collect data and information in this study were documents related to research and analysis of the textbooks examined by researchers. Findings- This research shows that the book